Simulation and Experimental Validation of Hydrogen Evolution Reaction using Titanium Carbide Supported, Platinum Doped Tetrahedral Amorphous Carbon Electrode - Harunal Rejan, Ramji (UNIMAS, 2023)
This work presented the use of commercial software COMSOL Multiphysics to simulate and solve the Volmer - Heyrovsky –Tafel mechanistic steps for hydrogen evolution reaction (HER). The first study will address the reliability of COMSOL to provide accurate and precise results for electrochemistry problem. The developed model is for classical cyclic voltammetry of redox reaction (E). In this study, mesh refinement with its consequent number of elements (noe), computation time (tcom), and current, I(t) was compared on the 1-dimension (1D), 2-dimension (2D) axisymmetric, and 3-dimension (3D) model. This study proved the software's consistency to produce less than 3% error between simulation and analytical results across all dimensions. By using a relative tolerance (rtol) value of 1×10-8 with very concentrated custom meshing, a 3D model yielded a result with an error of 2.5% compared to analytical solution. It has the drawback of taking 40 times longer to complete. A slight discrepancy between 2D axisymmetric and 3D simulation results on finest meshing recorded to have less than 3% difference due to CPU memory limit. The use of adaptive meshing on 2D axisymmetric and 3D model with coarse initial mesh reduces the error significantly by 32% and 50%, respectively. At the same time, the computation time, tcom increased by nearly ten times on the 2D axisymmetric model and five times on the 3D model. On the “finer” initial mesh, the simulation has reduced the error to near 0%. The rtol study shows that the value of 1×10-4 is adequate for 2D axisymmetric and 1×10-5 for both 1D and 3D. Further investigations on complex electrochemistry using this platform are well justified and highly recommended. Given the reliability of COMSOL presented in the first study, the second study implement similar approach to model the experiment by Glandut et. al (2015) on Titanium carbide (TiC) support, tetrahedral amorphous carbon doped platinum (taC:Pt) electrode for hydrogen evolution reaction. The developed model was tested for surface diffusion in 2D and surface diffusion with edge effect in 3D. The simulation results show that kinetic parameters permutation with surface diffusivity shows some increased in current output but was unable to achieve the current output obtained from the experiment. However, the introduction of edge effect on the side of taC:Pt on TiC support would significantly increase the current output with great coherency to the experimental result. The edge exhibits kinetic properties unlike both TiC or taC:Pt. The kinetic parameters were determined using the simulation and a dataset was found to show great coherency with the experimental result. Surface diffusion was rendered negligible because negligible compared to the high kinetic parameters on the edge in comparison to the TiC and taC:Pt surface.